2021
DOI: 10.31219/osf.io/zs7dq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Science Communication in Light of Moral and Social Concerns: Testing a Statistical Physics Model of Belief Change

Abstract: Most efforts to increase public acceptance of scientific facts have focused on providing transparent factual information. While this is essential for enabling people to make informed decisions, evidence is mixed about the effectiveness of facts alone for modifying beliefs. To enable more effective science communication, we need a better understanding of how moral and social considerations affect belief change beyond facts. In two longitudinal studies with a total of 1,673 participants, we experiment with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…We provide two empirical examples. One example (figure 2 b ) involves beliefs about safety of GM food, empirically measured two times in each of the three waves of a longitudinal survey on a national sample of N = 531 participants [161]. Besides this focal belief, in each wave, participants also reported 12 other beliefs about their individual moral issues related to GM food [162], and perceived beliefs of different social groups (family, online community, scientists, doctors, etc.).…”
Section: Main Components Of Belief Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We provide two empirical examples. One example (figure 2 b ) involves beliefs about safety of GM food, empirically measured two times in each of the three waves of a longitudinal survey on a national sample of N = 531 participants [161]. Besides this focal belief, in each wave, participants also reported 12 other beliefs about their individual moral issues related to GM food [162], and perceived beliefs of different social groups (family, online community, scientists, doctors, etc.).…”
Section: Main Components Of Belief Dynamicsmentioning
confidence: 99%
“…Parameters w and β are fitted with a grid search procedure (ranges: 0 ≤ w ≤ 1, and 0 ≤ β ≤ 100) for each time point on a random half of the participants, so that they minimize the deviation between modelled and actually measured focal beliefs (inspection of the deviations showed that only one parameter combination minimized the deviation between model and data). Here we present belief trends in the group of participants who received only the basic scientific information about the safety of GM food (figure 2b; for further results, see [161]). On average across time points, parameters w and β for this group are estimated at 0.57 and 23, respectively, suggesting a stronger weight on social dissonance and a moderate amount of uncertainty in belief updating process.…”
Section: Main Components Of Belief Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models tend to consider either the dissonance between moral and social beliefs using the concept of energy from statistical physics without considering the relationships between these beliefs (34), or the network imbalance between personal and social beliefs (e.g., belief A is positively connected to beliefs B and C, but beliefs B and C are negatively connected) (35)(36)(37). Dissonance-based models can explain belief change using estimated energies from reported moral and social beliefs (38). However, these models do not take into account the network structure of interrelated moral and social beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, scientists have never had access to so much empirical data about different aspects of human cognition and sociality as today. It is now more convenient than ever to obtain data from group experiments and observational studies [ 266 ], historical and archaeological data, ethnographic data, mobile phone data [ 267 ] and other sensing methods [ 268 ], to longitudinal surveys [ 269 , 270 ], and analyses of large textual corpora and other by-products of human interactions (e.g. [ 271 , 272 ]).…”
Section: Studying Collective Adaptationmentioning
confidence: 99%